Concerns Affecting Computer Usage by County Extension Educators in Florida - Kathleen C. Ruppert; Arlene Z. Stewart (Journal of Applied Communications, 1997)
The Florida Cooperative Extension Service continues to develop and provide information to extension educators and their clientele via computer.